Exploring Higher Education Students’ Intercultural Communication Competence - Enni Erawati Saragih; Movi Riana Rahmawanti; Amalul Umam (Journal of English Education and Teaching, 2023)
Globalization has made intercultural communication a necessity; it is the compelling urgency for students in 21st century English education. Intercultural Communication Competence intercultural communication competence is essential so the students could communicate globally within various cultural backgrounds. Intercultural communication competence allows students to communicate well in any circumstances, manage their effective learning, and adjust effectively to more extensive and multiple communities by recognizing their level of intercultural communication competence. The study is undertaken to discover an accurate picture of Higher Students' level of Intercultural Communication Competence and map their ability to communicate between culture. This study will employ a case study as the research methodology. Online questionnaires and interviews were used to explore students' level of I intercultural communication competence. There are some results of this study, one of them is most of the students have a good level of Intercultural Communicative Competence. Most of them have excellent cultural knowledge and sensitivity that will help them develops their professionalism, communication, and their learning in particular.